Desafios contemporâneos ao desenvolvimento do mercado da arte frente ao fenômeno da lavagem de dinheiro - Câmara Neto, Hamilton Calazans (2019)
The art market has peculiarities that seem to promote a relationship with organized crime aimed at money laundering and the concealment of assets. That happens because the lack of regulation, universality, the ease of transport and the price subjectivity of traded goods. This panorama is, until then, little discussed, and the present work aims to associate the concepts of development and sustainability to the art market, pointing out characteristics capable of demonstrating their influence both economically and sociologically, besides analyzing legal provisions capable of protecting from criminal practices while also promoting a continuity and expansion in a healthy, lawful and transparent manner. This study made methodological use of the international and national specialized literature, with a view to presenting the illegality of conduct and the conjuncture in which they occur when negotiating, transferring and guarding artistic works. From this perspective, it detail the legal regulations related to anti-washing policies at the international and national levels, such as Law no. 9.613/98, updated by Law no. 12.683/2012, and the concepts exposed by Law no. 12.850/2013, as well as the adoption of compliance programs, which insert an effective preservation of ethics and provide the conditions of equality between investors and consumers. Iconic cases of corruption and money laundering investigations, in Brazil, outlined by Lava Jato Operation, and in other nations, are exemplified for discussion of means and possible investigative techniques to be used in repression. to this criminal transgression through the art market. From this analysis, it is proposed possible solutions to be discussed and applied, such as criminal policy of legal, social, educational and economic character, which may face this criminal phenomenon and have a focus on the completeness, maintenance and recognition of this trade as instrument of preservation of History and of organization and promotion of lawful, competitive and regulated commercial activity. Thus, this work seeks to contribute to the fight against criminal practices in the art market, as well as to the valorization and development of Economic Criminal Law.